Shallow water Tanaidae (Crustacea: Tanaidacea) of Australia - Edgar, Graham J. (Zootaxa, 2008)
Investigation of shallow reef habitats around Australia revealed an extremely rich tanaid (Crustacea: Tanaidacea: Tanaidae) fauna. A total of 21 species in the family are now recognised from the Australian continent and Tasmania— about one-third of tanaids known worldwide. In this study, 15 species are diagnosed, including a new genus, Austrotanais g. sp., and twelve new species, Austrotanais rileyi n. sp., Sinelobus barretti g. sp., Zeuxoides lasti n. sp., Zeuxoides lauriebourqueae n. sp., Zeuxoides mawbeyi n. sp., Zeuxo russi n. sp., Zeuxo belli n. sp., Zeuxo kirkmani n. sp., Zeuxo odohertyae n. sp., Zeuxo mooneyi n. sp., Zeuxo shepherdi n. sp. and Pancoloides moverleyi n. sp. Keys are provided to local genera and species.